Pengaruh Kualitas Sumber Daya Manusia, Sistem Pengendalian Internal, Dan Pemanfaatan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan - Ni Komang Ayu Diah Astari; Ni Komang Sumadi; Ni Ketut Muliati (UNHI Press, 2023)
Cooperatives as an institution that are included in microfinance institutions have a very important role in Indonesia. It is very important for a cooperative to be able to create good financial reports which must contain various forms of real and honest information. This research will discuss the factors that can cause the quality of cooperative financial reports to be better, such as the quality of human resources, a control system that exists within the institution, and the use of available information systems. This research was conducted in all cooperatives in Klungkung District with a population of 718 employees, 98 of which were used as samples. This stage of research uses multiple linear regression analysis with the results that it is true that in the process of improving the quality of financial reports in cooperatives, qualified employees are needed. In cooperatives, it is very important to be supported by human resources with good competence to support the process of making financial reports. The quality of financial reports must also be supported by a good control system. In cooperatives it is necessary to create an internal control system to monitor the performance and activities of the cooperative so that all the desired final results are achieved. Increasingly sophisticated technology also needs to be utilized to facilitate the work process of employees. Wise use of technology will make it easier for cooperatives to produce fast and detailed financial reports so as to create a good financial report.